Postoperative pain behaviours in rabbits following orthopaedic surgery and effect of observer presence - Pinho, Renata Haddad [UNESP]; Leach, Matthew C.; Minto, Bruno Watanabe [UNESP]; Del Lama Rocha, Fabiana [UNESP]; Luna, Stelio Pacca Loureiro [UNESP] (Public Library of Science (PLoS), 2020)
Rabbits are widely used in studies focusing on pain. However, pain is undertreated in this species and one possible factor to explain this is the lack of evaluation methods. The objective of this study was to identify behaviours related to orthopaedic pain in rabbits and to evaluate the influence of the presence of an observer on these behaviours. Twenty-eight rabbits undergoing orthopaedic surgery and filmed 24 hours before surgery, and 1 hour (before rescue analgesia), 4 hours (3 hours after rescue analgesia), and 24 hours post-recovery were observed in the presence and absence of an observer. The frequency and/or duration of behaviours were compared over time and between the presence and absence of the observer using the Friedman and Wilcoxon tests respectively. Data are expressed as median and interquartile range and a significant difference was considered when p<0.05. At 1 hour post-recovery, the rabbits showed reduced activity, hopping, change posture, position in the cage, explore, and open eyes in both the presence and absence of the observer. In the absence of the observer, quadrupedal posture, interact with pinecone, and eat carrot also decreased, while wince behaviour increased. In the presence of the observer, before surgery, the rabbits were less active (Presence-280; 162-300, Absence-300; 300-300) and presented a lower duration of explore (Presence-3; 0-32, Absence-40; 4-63). Post-recovery the rabbits flinched less (Presence-0; 0-0, Absence-0; 0-1) and suspended the affected limb less (Presence-0; 0-0, Absence-0; 0-65). After rescue analgesia the rabbits put weight on and raised the affected limb less (Presence-0; 0-0, Absence-0; 0-2) and licked the affected area less (Presence-0; 0-0, Absence-0; 0-2). These findings demonstrate that the presence of the observer inhibited pain-free behaviours in the rabbits, leading to a false impression of pain, and after the surgery the rabbits masked some pain signs related to the affected area.